Synthesis and utilization of ferrocene chiral auxiliaries - Weitgenant, Jeremy Aaron, author; Hegedus, L. S., advisor (Colorado State University. Libraries, 2002)
With the goal to produce β-amino acids in an asymmetric fashion, S-(I-ferrocenyl-2-methylpropyl)amine was condensed with ethyl acetoacetate, which provided a novel ferrocenyl enamine ester. Two consecutive alkylation reactions in the α-position gave low or no enantioselectivity.

The above result led to the synthesis of a novel chiral ferrccenvl enamide that underwent a formal [2+2] cvcloaddition with (methyl)(methoxy[chromium carbene complex that resulted in the formation of a cyclobutanone as a single diastereomer. Ring expansion followed by cleavage of the novel ferrocenyl auxiliary gave an amine-substituted cyclopentanone and allowed for the recycling of the chiral auxiliary.

The success of the above example allowed for the synthesis of a novel ferrocenyl lactam that when alkylated with ethyl bromoacetate followed by two consecutive alkylations in the α-position gave disubstituted ferrocenyl esters in diastereomeric ratios of ~4.9:1 to >25:1 in moderate to high yields. Cleavage of the ferrocenyl auxiliary gave α,α-disubstituted α-amino esters in enantiomeric excesses of 65% to 96% in moderate yields and once again allowed for the recycling of the auxiliary.
Keywords: organic chemistry